An Overview of Surgical Strategies for Treating Obesity - Jędrasek, Aleksandra; Barg, Marta; Biały-Karbowniczek, Julia; Bartela, Agata; Wojtyła, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction: In the last few years, obesity has become a central issue with more than 2.6 billion people worldwide being overweight or obese. While the risks associated with this condition and its rising significance are widely known, the effect of this attention on screening and treatment remains unsatisfying. This paper explores multiple treatment strategies and evaluates their effectiveness in preventing obesity-related complications. Review methods: We conducted our study as a literature review, with data being gathered via PubMed and Embase. The state of knowledge: Physical activity, behavioral therapy, and proper nutrition remain the foundation for obesity therapy. However, in many cases these approaches are insufficient. Recently, there has been a dynamic development of bariatric surgery, which in comparison to lifestyle modification, results in better long-term effects and improved quality of life. New surgery procedures, such as sleeve gastrectomy and adjustable gastric banding, have shown to be one of the most effective, but they carry a risk of complications. Conclusions: Growing treatment options allow doctors to choose more targeted strategies, based on the patient’s risk factors, overall health status, and compliance. Improvements in surgery, especially laparoscopic techniques have opened new possibilities for patients with morbid obesity.